INTERPRETASI HUKUM EKONOMI SYARIAH DALAM FIQH ANGGARAN BERDASARKAN AKUNTANSI SYARIAH - Dyah Syahira Tara Dewi; Aisya Rahma Izzati; Kamilatul Aqilah; Hendyawan Hendyawan; Gunawan Aji (MSJ : Majority Science Journal, 2023)
The current global economic impact has an important impact on the welfare of a country. It's the same with corruption. In modern times, the stage of development of corrupt practices has actually started since Indonesia's independence from colonialism and even now it is not difficult to find. By using a library data collection method whose main objective is the interpretation of Syaria Economic law in budgets based on sharia accounting, which of course involves many things such as the principle of monotheism, the principle of maslahah, the principle of justice and also the urgency of budget fiqh.The application of basic principles of Islamic law in budget preparation is very important in efforts to prevent budget leaks. In this context, the existence of a fiqh budget plays an important role, not only for the interests of individuals but also for society.